Penerapan Media Belajar Berbasis Teknologi Dalam Mengembangkan Kemampuan Mengingat Siswa Pada Pembelajaran Daring - Ruth Yohana Purba; Jessica Elfani Bermuli (Mahesa Research Center, 2022)
Remembering is the ability to focus on knowledge and it really makes a difference in the learning process. It's in the online learning period today, many students have weak remember skills, including elementary school students. Weak remember skills in elementary school students will cause them difficulty in achieving learning goals in the cognitive domain. The application of technology-based learning media that is one solution can be done to abilities students remember skills, especially for elementary school students who are still thinking concretely. The ability to remember was a present of God that should be developed as a form of gratitude to God and used to glorify God. The purpose of this article is to analyze the application of technology-based learning media in developing students remember skills. The method used was qualitative descriptive and literary studies. Based on the results of the research, the application of learning media that utilizes technology has a significant influence on the development of students' memory skills. This is evident from the accuracy of student responses when answering questions posed by the teacher through review questions and guided exercises containing the material they have studied previously. In addition, student learning outcomes also showed an increase which can be seen through the results of the class average score from 79.5 to 86.9 and 83.3 after the media was applied.